Background: Ureteric injury during a surgical procedure is a serious complication with significant morbidity. The objective of this research was to study the aetiology, clinical features and management of iatrogenic ureteric injuries after open surgical p - Durrani, Saadia Nawaz; Rehman, Ata ur; Khan, Sarhad; Ullah, Hazrat; Khan, Muhammad Kamran; ullah, Anayat (Journal of Ayub Medical College Abbottabad, 2013)
Background: Ureteric injury during a surgical procedure is a serious complication with significant morbidity. The objective of this research was to study the aetiology, clinical features and management of iatrogenic ureteric injuries after open surgical procedures. Methods: This descriptive study was carried out in the Urology and Transplant unit of Institute of Kidney Diseases, Peshawar, from 1st August 2008 to 30th April 2011. Patients with clinical diagnosis of ureteral trauma due to open surgical procedures were included in the study through convenient sampling after informed consent. Important variables under study were: aetiology of ureteric injury, presenting features, time from injury to diagnosis, type of ureteric injury, treatment options, and outcome of treatment. Follow up was at 1, 3, 6 and 12 months. Results: The study included 43 patients; 33 (76.7%) were females and 10 (23.3%) males. Abdominal hysterectomy was the commonest cause 20 (46.5%) of ureteric injury. Common presenting features were urinary incontinence 13 (30.23%), flank pain 7 (16.3%) and anuria 10 (23.3%). Median time from ureteric injury to urological referral was 10 days. Distal ureter was most commonly injured. Percutaneous nephrostomy was carried out in 14 (32.5%) cases. Ureteroscopic ureteric stenting was successful in 5 (11.6%) cases. Ureteroneocystostomy was carried out 25 (58%) cases. Two (4.7%) cases presented very late with non-functioning kidneys and required nephrectomy. Patients developing ureteric stricture after ureteroneocystostomy were managed successfully by endo-urological procedures. Renal function remained stable in all the patients during follow-up and there was no mortality. Conclusion: Timely recognition of ureteric injury and its management is associated with good outcome and decreased morbidity. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; letter-spacing: -.2pt; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Keywords<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; letter-spacing: -.2pt; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">: Ureteric injuries, iatrogenic, complication, open surgery, management <!–[if !supportLists]–>1. <!–[endif]–>St Lezin MA, Stoller ML: Surgical ureteral injuries. Urology 1991;38:497-506. <!–[if !supportLists]–>2. <!–[endif]–>Carver BS, Bozeman CB, Venable DD. Ureteral injury due to penetrating trauma. South Med J 2004;97:462-4. <!–[if !supportLists]–>3. <!–[endif]–>Fraga GP, Borges GM, Mantovani M, Ferreira U, Laurito TL, Netto NR Jr. Penetrating ureteral trauma. Int Braz J Urol2007;33:142-50. <!–[if !supportLists]–>4. <!–[endif]–>Al-Awadi K, Kehinde EO, Al-Hunayan A, Al-Khayat A. Iatrogenic ureteric injuries: incidence, aetiological factors and the effect of early management on subsequent outcome. Int Urol Nephrol 2005;37:235-41. <!–[if !supportLists]–>5. <!–[endif]–>Geavlete P, Georgescu D, NiÅ£Äƒ G, Mirciulescu V, Cauni V. Complications of 2735 retrograde semirigid ureteroscopy procedures: a single-center experience. J Endourol 2006;20:179-85. <!–[if !supportLists]–>6. <!–[endif]–>Schimpf MO, Gottenger EE, Wagner JR. Universal ureteral stent placement at hysterectomy to identify ureteral injury: a decision analysis. BJOG 2008;115:1151-8. <!–[if !supportLists]–>7. <!–[endif]–>Chou MT, Wang CJ, Lien RC. Prophylactic ureteral catheterization in gynaecologic surgery: a 12-year randomized trial in a community hospital. Int Urogynecol J Pelvic Floor Dysfunct 2009;20:689-93. <!–[if !supportLists]–>8. <!–[endif]–>Kim J.-H, Moore C, Jones JS, Rackley R, Daneshgari F, Goldman H, et al. Management of ureteral injuries associated with vaginal surgery for pelvic organ prolapse. Int Urogynecol J 2006;17:531-5. <!–[if !supportLists]–>9. <!–[endif]–>Hammad FT, Alqaiwani KM, Shirodkar SS. The role of urologists in the management of urological injuries during obstetric and gynaecologic surgery. Int Urogynecol J Pelvic Floor Dysfunct 2010;21:1237-41. <!–[if !supportLists]–>10. <!–[endif]–>Rafique M, Arif MH. Management of iatrogenic ureteric injuries associated with gynaecological surgery. Int Urol Nephrol 2002;34:31-5. <!–[if !supportLists]–>11. <!–[endif]–>Anwar MS, Tariq M, Saeed K, Ghafoor T, Mustafa G. Causes of ureteric injuries and outcome of different surgical procedures for the repair of ureter. J Sheikh Zayed Med Coll 2010;1:16-20. <!–[if !supportLists]–>12. <!–[endif]–>Ghali AM, El Malik EM, Ibrahim AL, Ismail G, Rashid M. Ureteric injuries: diagnosis, management and outcome. J Trauma 1999;46:150-8. <!–[if !supportLists]–>13. <!–[endif]–>Mensah J, Klufio G, Ahiaku F, Osafo C, Gepi-Attee S. Delayed recognition of bilateral ureteral injury after gynaecological surgery. Ghana Med J 2008; 42:133-6. <!–[if !supportLists]–>14. <!–[endif]–>Visco AG, Taber KH, Weidner AC, Barber MD, Myers ER. Cost-effectiveness of universal cystoscopy to identify Ureteral injury at hysterectomy. Obstet Gynecol 2001;97:685-92. <!–[if !supportLists]–>15. <!–[endif]–>Lask D, Abarbanel J, Luttwak Z, Manes A, Mukamel E. Changing trends in the management of iatrogenic ureteral injuries. J Urol 1995;154:1693-5. <!–[if !supportLists]–>16. <!–[endif]–>Tsai CK, Taylor FC, Beaghler MA. Endoscopic ureteroureterostomy: longterm followup using a new technique. J Urol 2000;164:332-5. <!–[if !supportLists]–>17. <!–[endif]–>Routh JC, Tollefson MK, Ashley RA, Husmann DA. Iatrogenic ureteral injury: can adult repair techniques be used on children? J Pediatr Urol 2009;5:53-5. <span style="font-size: 8.0pt; mso-bidi-font-size: 12.0pt; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; letter-spacing: -.2pt; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Selzmann AA, Spirnak JP. Iatrogenic ureteral injuries: a 20-year experience in treating 165 injuries. J Urol 1995;155:878-81.